Metal film and electronic component

By adhering silica particles below 100 nm to the surface of the metal foil, the adhesion between the copper foil and the insulating layer is improved, the problem of insufficient adhesion in the prior art is solved, and good bonding strength and high frequency are achieved. characteristic.

CN119487980APending Publication Date: 2025-02-18KYOCERA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, there is room for improvement in the adhesion between the copper foil and the insulating layer, and it is difficult to achieve good bonding strength.

Method used

A metal film consisting of a metal foil and a plurality of silica particles having an average particle diameter of 100 nm or less is used, and the silica particles are in contact with the surface of the metal foil to improve adhesion.

Benefits of technology

Good bonding strength to the insulating layer is achieved, and the dielectric characteristics are reduced in electronic components, maintaining high-frequency characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487980A_ABST
    Figure CN119487980A_ABST
Patent Text Reader

Abstract

The metal film is provided with a metal foil and a plurality of silica particles having an average particle diameter of 100 nm or less. The plurality of silica particles are in contact with the surface of the metal foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a metal film and an electronic component. Background Art

[0002] Conventionally, metal foils such as copper foil have been used in the conductor layers of wiring boards. For example, a technique for forming a wiring board by attaching copper foil to the surface of an insulating substrate using an adhesive mixed with rigid particles is disclosed (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 59-194487. Summary of the Invention

[0006] The metal film of the present disclosure includes a metal foil and a plurality of silica particles having an average particle size of 100 nm or less. The plurality of silica particles are in contact with the surface of the metal foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 2 is a cross-sectional view showing an example of the structure of the metal film according to the embodiment.

[0008] Figure 2 This is a cross-sectional view showing an example of the configuration of a wiring substrate according to the embodiment. DETAILED DESCRIPTION

[0009] The following describes embodiments of the metal film and electronic component disclosed in this application with reference to the accompanying drawings. It should be noted that the present disclosure is not limited to the embodiments shown below. Furthermore, the various embodiments can be combined as appropriate within the scope of the non-conflicting treatment content. In the following embodiments, identical parts are denoted by the same reference numerals, and duplicate descriptions are omitted.

[0010] Conventionally, metal foils such as copper foil have been used in the conductor layers of wiring boards. For example, a technique is disclosed in which a wiring board is formed by attaching copper foil to the surface of an insulating base material using an adhesive mixed with rigid particles.

[0011] However, the conventional technology still has room for improvement in terms of improving the adhesion between the insulating layer and the metal foil. Therefore, a technology that can solve the above-mentioned problems and achieve good bonding strength to the insulating layer is desired.

[0012] (metal film)

[0013] Figure 1 : is a cross-sectional view showing an example of the metal film 1 according to the embodiment. Figure 1(a) is a cross-sectional view showing the entire metal film 1, Figure 1 (b) is a cross-sectional view showing an enlarged view of the surface of the metal film 1 .

[0014] like Figure 1 As shown, the metal film 1 of the embodiment includes a metal foil 10 and a plurality of silica particles 11 .

[0015] The metal foil 10 is in the form of a thin film (foil) and contains a metal as its main component. The metal foil 10 has a main surface 10a. The main surface 10a is an example of a surface. The metal foil 10 is not particularly limited; examples thereof include copper foils such as electrolytic copper foil and rolled copper foil; nickel foil; and composite foils formed by overlapping these metal foils.

[0016] The thickness of the metal foil 10 is not particularly limited, and may be, for example, approximately 5 μm to 105 μm. The surface roughness of the metal foil 10 is not particularly limited, and may be, for example, 0.5 μm or less, or 0.3 μm or less. Alternatively, the surface roughness of the metal foil 10 may be 0.001 μm or greater.

[0017] The silica particles 11 are spherical and contain silicon dioxide (SiO 2 ) as a main component. The average particle size of the plurality of silica particles 11 may be 100 nm or less, or 20 nm or less.

[0018] The particle size range of the plurality of silica particles 11 may be, for example, the range of D10 (10% cumulative) to D90 (90% cumulative) when measuring the particle size distribution, from 5 nm to 50 nm, or from 10 nm to 30 nm.

[0019] Here, in the metal film 1 of the embodiment, as Figure 1 As shown in (b), a plurality of nanometer-sized silica particles 11 may also be in contact with the main surface 10a of the metal foil 10. Thus, the insulating layer 12 (see Figure 2 ) is located in contact with the main surface 10a of the metal foil 10, the adhesion between the metal foil 10 and the insulating layer 12 can be improved.

[0020] This is because the metal film 1 of the embodiment is composed of the metal foil 10 and the plurality of silica particles 11, and therefore has almost no constituent elements that volatilize during the firing process. Even if the firing process is performed to form the wiring substrate 2 (see Figure 2 ) After that, the bonding force between the metal foil 10 and the insulating layer 12 is also difficult to be damaged.

[0021] Furthermore, since the metal film 1 of the embodiment is configured by attaching a large number of nano-sized silica particles 11 to the main surface 10 a of the metal foil 10 , the nano-sized silica particles 11 exhibit high adhesion to the glass ceramic serving as the insulating layer 12 .

[0022] Therefore, according to the embodiment, a metal film 1 having good bonding strength to the insulating layer 12 can be realized. In the metal film 1 of the embodiment, the silica particles 11 may be bonded to only a portion of the surface of the metal foil 10 or to the entire surface of the metal foil 10.

[0023] Furthermore, in the embodiment, because the silica particles 11 contained in the metal film 1 are nanometer-sized, even if the silica particles 11 diffuse into the insulating layer 12 of the glass ceramic, the degradation of the dielectric properties of the insulating layer 12 can be minimized. Therefore, according to the embodiment, an electronic component with excellent high-frequency characteristics can be realized. The nanometer-sized silica particles 11 are present at the interface between the insulating layer 12 of the glass ceramic and the metal foil 10.

[0024] In the embodiment, electrostatic attraction can also act between the metal foil 10 and the silica particles 11. This allows for a strong bond between the metal foil 10 and the silica particles 11 without the use of a dissimilar material such as an adhesive. In this case, an electrostatic scanner is used to evaluate the electrostatic attraction between the metal foil 10 and the silica particles 11. An electrostatic scanner can visualize the generation of static electricity between the metal foil 10 and the silica particles 11.

[0025] Therefore, according to the embodiment, since the shedding of the silicon dioxide particles 11 can be reduced when the metal film 1 is handled, the metal film 1 can be easily handled in the manufacturing process of the electronic component.

[0026] In addition, in the embodiment, Figure 1 As shown, the spherical silica particles 11 are in point contact with the metal foil 10 , and portions of the metal foil 10 that are not in contact with the silica particles 11 may be exposed.

[0027] Here, the point contact between the spherical silica particles 11 and the metal foil 10 does not refer to the length of the outline interpreted as a point, as when two true spheres come into contact. In reality, although the silica particles 11 are spherical, they are not theoretically true spheres, but rather a shape close to a true sphere.

[0028] Therefore, the surface of silica particles 11 includes a portion having a greater curvature than that calculated from the average radius of silica particles 11. The contact area between this portion and metal foil 10 is not a point, but a surface having a predetermined area. When the length of the outline of silica particles 11 is 100, the ratio of the area of ​​contact between metal foil 10 and silica particles 11 can be 1 or more and 20 or less, or 5 or more and 10 or less.

[0029] The relative dielectric constant of silica particles 11 is approximately 2.0 to 2.4. Furthermore, because metal foil 10 is in contact with the low-dielectric-constant silica particles 11, even when the relative dielectric constant of the glass-ceramic insulating layer 12 is higher than that of the silica particles 11, a conductive layer with high interfacial conductivity can be achieved by utilizing the contact area with silica particles 11. The silica particles 11 are dispersed in a planar manner at the interface between the insulating layer 12 and the metal foil 10.

[0030] In the embodiment, the silica particles 11 may have a neck (not shown) at the portion in contact with the metal foil 10 . That is, some silica particles 11 may have a neck between themselves and the metal foil 10 .

[0031] This allows for a stronger bond between the metal foil 10 and the silica particles 11 without intervening a different material such as an adhesive. Therefore, according to the embodiment, the metal film 1 can be handled more easily in the manufacturing process of the electronic component.

[0032] Furthermore, in the embodiment, when the unit area of ​​the metal foil 10 is set to 1 in a plan view, the area ratio of the plurality of silica particles 11 may be 1% or more and 60% or less. This allows for a balance between the adhesion between the metal foil 10 and the insulating layer 12 and electrical properties (e.g., interface conductivity) in the electronic component.

[0033] For example, when the area ratio of the plurality of silica particles 11 is 1%, in a 10 μm×10 μm (ie, an area of ​​100 μm 2 ) in the metal foil 10, a plurality of silica particles 11 occupy 1 μm 2 area.

[0034] Furthermore, if the diameter of the silica particle 11 is 20 nm, the area of ​​the silica particle 11 in a plan view is 3.14×10 -4 μm 2 .

[0035] Therefore, when the area ratio of the plurality of silica particles 11 is 1%, there are 1÷(3.14×10 -4 ) = about 3184 silica particles 11.

[0036] As described above, in the embodiment, since a large number of silica particles 11 are present on the main surface 10 a of the metal foil 10 , high adhesive strength can be achieved between the metal foil 10 and the insulating layer 12 .

[0037] Furthermore, by setting the area ratio of the plurality of silica particles 11 to 60% or less, all silica particles 11 can be dispersed without overlapping on the main surface 10a of the metal foil 10. The plurality of silica particles 11 are dispersed without overlapping in the thickness direction of the metal foil 10.

[0038] In the embodiment, the metal foil 10 may contain copper or nickel as a main component. When the metal foil 10 contains copper as a main component, high interface conductivity and low DC resistance can be obtained as a conductor layer of the wiring board 2.

[0039] Furthermore, when the metal foil 10 is mainly composed of nickel, it can be used as a low-resistance conductor that can withstand high temperatures, for example, as an electrode material for a fuel cell. Furthermore, when the metal foil 10 is mainly composed of nickel, it is also useful as an internal electrode layer for a capacitor.

[0040] In the embodiment, the silica particles 11 may be aggregates of a plurality of primary particles having an average particle size of 1 nm to 5 nm. Since the silica particles 11 are formed from fine primary particles, the silica particles 11 have higher surface energy.

[0041] This allows for a stronger bond between the metal foil 10 and the silica particles 11 without intervening a different material such as an adhesive. Therefore, according to the embodiment, the metal film 1 can be handled more easily in the manufacturing process of the electronic component.

[0042] (Wiring substrate)

[0043] Figure 2 1 is a cross-sectional view showing an example of the structure of the wiring substrate 2 according to the embodiment. Figure 2 (a) is a cross-sectional view showing the entire wiring substrate 2, Figure 2 (b) is an enlarged cross-sectional view of the interface between the metal foil 10 and the insulating layer 12 in the wiring substrate 2. The wiring substrate 2 is an example of an electronic component.

[0044] like Figure 2As shown, the wiring board 2 of the embodiment includes a metal film 1 and an insulating layer 12. That is, the wiring board 2 of the embodiment includes a metal foil 10, a plurality of silica particles 11, and an insulating layer 12.

[0045] The insulating layer 12 is a thin plate-shaped material containing an insulator as a main component. The material of the insulating layer 12 is not particularly limited, and examples thereof include various ceramic materials such as glass ceramics and zirconia-based ceramics, and organic resins.

[0046] Furthermore, in the wiring board 2 of the embodiment, the metal foil 10 functions as a wiring layer. Thus, in the wiring board 2 of the embodiment, since the wiring layer is composed of the metal foil 10 rather than the metallized layer, a wiring board 2 having a conductive layer exhibiting high conductivity can be obtained. In this case, the metal foil 10 may also contain copper as a main component.

[0047] Furthermore, in the wiring board 2 of the embodiment, the metal foil 10 and the insulating layer 12 are bonded so that the main surface 10a of the metal foil 10 is in contact with the main surface 12a of the insulating layer 12. That is, in the embodiment, the metal foil 10 is bonded to the insulating layer 12 via the plurality of silica particles 11. Therefore, in the embodiment, as described above, the adhesive strength between the metal foil 10 and the insulating layer 12 can be improved.

[0048] Furthermore, in the embodiment, since the silica particles 11 contained in the metal film 1 are nanometer-sized, even if the silica particles 11 diffuse into the insulating layer 12 of the glass ceramic, the degradation of the dielectric properties of the insulating layer 12 can be reduced. Therefore, according to the embodiment, a wiring board 2 having excellent high-frequency characteristics can be realized.

[0049] (Electronic components)

[0050] In addition, the present disclosure can also be applied to the following electronic components. This electronic component also has a metal foil 10 (see Figure 2 ), a plurality of silica particles 11 (refer to Figure 2 ) and the insulating layer 12 (refer to Figure 2 ).

[0051] The electronic component may also have a structure in which metal foil 10 is arranged on main surface 12a of insulating layer 12, similar to the wiring board 2 described above. Alternatively, metal foil 10 may be arranged on both surfaces of insulating layer 12.

[0052] In this case, nickel is preferably used as the material of the metal foil 10. When nickel is used as the material of the metal foil 10, a ceramic material exhibiting dielectric properties is preferably used as the material of the insulating layer. A ceramic material exhibiting dielectric properties may also be referred to as dielectric ceramic.

[0053] Examples of dielectric ceramics include ceramic materials containing barium titanate as a main component. "Main component" here refers to the presence of 80 mol% or more of barium titanate in the dielectric ceramic. Dielectric ceramics are suitable, for example, for use as dielectric layers in multilayer ceramic capacitors.

[0054] (Fuel Cell)

[0055] In addition, the present disclosure can also be applied to the following fuel cell. This fuel cell also has a metal foil 10 (see Figure 2 ), a plurality of silica particles 11 (refer to Figure 2 ), and the insulating layer 12 (refer to Figure 2 ).

[0056] The fuel cell also includes a fuel electrode and a support. The fuel electrode comprises a solid electrolyte material and nickel. In the fuel cell, the fuel electrode material is primarily composed of zirconium oxide. In this case, the metal foil 10 is preferably made of nickel. In this case, the nickel conductor is also preferably one with a plurality of silica particles 11 disposed on its surface.

[0057] Example

[0058] The following describes embodiments of the present disclosure in detail. It should be noted that, in the embodiments described below, a metal film having copper foil is first described, followed by a wiring substrate having an insulating layer composed of the metal film and glass ceramic. However, the present disclosure is not limited to the following embodiments.

[0059] (Sample 1)

[0060] First, 18 μm thick copper foil was prepared as the metal foil material. Also, a plurality of silica particles with an average particle size of 20 nm were prepared. The silica particles were aggregates of primary particles with a particle size of approximately 1 nm to 10 nm.

[0061] Then, the prepared copper foil was subjected to a treatment for removing the oxide film on the surface with hydrochloric acid, followed by alkali washing and water washing.

[0062] Then, the copper foil after the water washing process was subjected to a process of bonding a plurality of silica particles. Specifically, first, silica particles were prepared in an amount of about 50% by area on the main surface of the copper foil.

[0063] Then, copper foil was attached to a metal substrate, a metal frame was placed around the copper foil, the above amount of silica particles was put into the frame, and ultrasonic waves were applied to the metal substrate to disperse the silica particles in the copper foil.

[0064] After the dispersion treatment, a stainless steel plate was placed on the silica particles and pressed against them at a predetermined pressure via the plate. This produced a metal film of Sample 1 with a plurality of silica particles attached to the main surface. The ratio of the attached silica particles to the total amount of silica particles introduced into the frame was approximately 10% to 20%.

[0065] Then, using the metal film obtained above, a wiring board of Sample 1 was produced. First, glass ceramic green sheets having a thickness of 0.2 mm were prepared, and six of the green sheets were stacked.

[0066] Then, metal films were attached to both main surfaces of the green sheet. Note that, at this time, the green sheet and the metal films were arranged so that the silica particles of the metal films adhered to the green sheet.

[0067] The obtained stack of green sheets and metal films was then fired in a reducing atmosphere using a hydrogen-nitrogen mixed gas at a maximum temperature of 930° C. for a holding time of 2 hours.

[0068] The copper foil was then etched to form the sintered copper foil into a predetermined shape. This etching was performed using a conventional method. Thus, a wiring board of Sample 1 was obtained.

[0069] (Sample 2)

[0070] The metal film and wiring board of Sample 2 were obtained by the same method and conditions as Sample 1 except that borosilicate glass powder with an average particle size of 1 μm was used instead of nano-sized silica particles in the metal film production step.

[0071] (Sample 3)

[0072] In the metal film production step, a metal film and a wiring board of Sample 3 were obtained by the same method and conditions as Sample 1, except that the nano-sized silica particles were attached to the copper foil using an organic resin adhesive.

[0073] (Various reviews)

[0074] The metal films and wiring boards of Samples 1 to 3 obtained above were then visually inspected. The results showed that in the metal film of Sample 1, the silica particles were firmly fixed to the copper foil and did not fall off the copper foil even when the metal film was handled. In the metal film of Sample 1, the silica particles were bonded to the copper foil by electrostatic forces and van der Waals forces.

[0075] The metal films and wiring boards of Samples 1 to 3 obtained above were cut, and the cut surfaces were embedded in resin, mirror-polished, and observed using a scanning electron microscope (SEM). The results revealed that in the metal film of Sample 1, multiple silica particles were observed, firmly bonded to the copper foil via neck bonds.

[0076] In the wiring board of Sample 1, the silica particles were in particle form and present between the copper foil and the glass ceramic, bonding the silica particles to the glass ceramic. In the wiring board of Sample 1, the area surrounding the neck-bonding portion of the silica particles was filled with glass ceramic.

[0077] As described above, in the wiring board of Sample 1, by using nano-sized silica particles as a binder on the copper foil, solid solution into the glass ceramic is suppressed, and the silica particles are firmly bonded to the copper foil in a particle state.

[0078] On the other hand, in the wiring board of Sample 2, the glass powder was dissolved in the insulating layer and was hardly present in the form of particles between the copper foil and the glass ceramic.

[0079] Furthermore, the presence or absence of conductor peeling in the wiring boards of Samples 1 to 3 obtained above was evaluated. As evaluation samples, samples were used in which copper foil was laminated on both sides of an insulating layer having a side of 10 mm to 50 mm.

[0080] Furthermore, the evaluation sample was first cut at approximately half its length in one direction, and the interfaces between the insulation layer and the copper foil in this cross-section were observed to evaluate for conductor peeling. If peeling was observed at one point, it was judged as "peeling was present," and if no peeling was observed at any interface, it was judged as "no peeling."

[0081] It should be noted that in the above determination, "peeling" refers to the situation where the length of the region between the insulation layer and the copper foil, which is at least 0.1 mm apart, is at least 1 mm. As a result, the wiring board of Sample 1 was determined to be "non-peeling," whereas the wiring boards of Samples 2 and 3 were determined to be "peeling."

[0082] The interface conductivity of the wiring substrates of Samples 1 to 3 obtained above was measured. The interface conductivity was measured using the dielectric cylindrical resonator method described below. The measurement samples used were wiring substrates with a diameter of 50 mm and copper foil formed on substantially the entire surface of both surfaces.

[0083] The dielectric cylinder resonator method is a method for measuring interface conductivity. An insulating layer with the aforementioned conductor formed therein is attached to both end faces or one end face of a dielectric cylinder made of a dielectric material with known relative permittivity and dielectric loss in a predetermined relationship to form a dielectric resonator. The dielectric resonator is then formed, and the conductivity at the interface between the copper foil and the insulating layer, i.e., the conductor interface, is measured.

[0084] The principle of this measurement method is that, in the case of an electromagnetic field resonator consisting of two parallel end faces of a dielectric cylinder having a specified dimension ratio (height h / diameter d), sandwiching a sufficiently large conductor plate (typically a conductor plate having a diameter D approximately three times the diameter d of the dielectric cylinder) to negligible edge effects, the high-frequency current flowing through the conductor plate in the TEomn resonance mode (hereinafter referred to as the TEomn mode) is distributed only along the short-circuit surface, i.e., the opposing surfaces of the dielectric and the conductor.

[0085] In a dielectric resonator, the high-frequency current flowing through a conductor in the TEomn mode (m=1, 2, 3, ..., n=1, 2, 3, ...) is distributed only at the interface between the conductor and the dielectric substrate, where the dielectric cylinder contacts the conductor. Therefore, the interface conductivity can be calculated from the measured resonant frequency f0 of the TEomn mode (m=1, 2, 3, ..., n=1, 2, 3, ...) and the unloaded Q and Qu. The interface conductivity was measured over a frequency range of 1 GHz to 49 GHz and evaluated as a relative value, with the interface conductivity in direct current (DC) set to 100%.

[0086] The results showed that the interface conductivity of the wiring board of Sample 1 was 80% or higher within the frequency range of 1 (GHz) to 49 (GHz). On the other hand, the interface conductivity of the wiring boards of Samples 2 and 3 was 80% within the frequency range of 1 (GHz) to 49 (GHz).

[0087] Furthermore, a thermal shock test was performed on the wiring boards of Samples 1 to 3 obtained above by immersing them in a heated solder bath for approximately 1 second. In this thermal shock test, the solder bath temperature was set at two temperatures: 325°C (i.e., ΔT = 300°C) and 355°C (i.e., ΔT = 330°C).

[0088] Furthermore, cracks in the wiring substrates were confirmed by observing samples obtained by cross-section grinding using a stereomicroscope. The results showed that while the wiring substrate of Sample 1 exhibited good thermal shock resistance under all temperature conditions, the wiring substrates of Samples 2 and 3 did not exhibit good thermal shock resistance under all temperature conditions.

[0089] While the embodiments of the present disclosure have been described above, the present disclosure is not limited to the aforementioned embodiments. Various modifications are possible without departing from the main purpose of the present disclosure. For example, the aforementioned embodiments illustrate an example in which a fine powder of silica particles is attached to the metal foil 10, but the present disclosure is not limited to this example.

[0090] For example, ceramic fine powder other than silicon dioxide (for example, alumina fine powder) may be attached to the metal foil 10. This also can achieve the same effects as those of the above-described embodiment.

[0091] Those skilled in the art will readily be able to deduce further effects or other embodiments. Therefore, the broader aspects of the present invention are not limited to the specific details and representative embodiments shown and described above. Therefore, various modifications may be made without departing from the spirit or scope of the general inventive concept as defined by the scope of the appended claims and their equivalents.

[0092] In addition, the present technology can adopt the following configurations.

[0093] (1) A metal film comprising a metal foil and a plurality of silica particles having an average particle size of 100 nm or less, wherein the plurality of silica particles are in contact with a surface of the metal foil.

[0094] (2) The metal film according to (1) above, wherein electrostatic attraction acts between the metal foil and the silica particles.

[0095] (3) The metal film according to (1) or (2) above, wherein the silica particles are spherical, the silica particles are in point contact with the metal foil, and portions of the metal foil not in contact with the silica particles are exposed.

[0096] (4) The metal film according to any one of (1) to (3), wherein the area ratio of the plurality of silica particles is 1% to 60% when the unit area of ​​the metal foil in a plan view is set to 1.

[0097] (5) The metal film according to any one of (1) to (4) above, wherein the metal foil contains copper or nickel as a main component.

[0098] (6) The metal film according to any one of (1) to (5), wherein the silica particles are aggregates of a plurality of primary particles having an average particle diameter of 1 nm to 5 nm.

[0099] (7) An electronic component comprising the metal film according to any one of (1) to (6) above and an insulating layer, wherein the metal foil is bonded to the insulating layer via a plurality of the silica particles.

[0100] (8) An electronic component according to (7) above, wherein the metal foil is composed of at least one metal foil selected from the group consisting of copper foils such as electrolytic copper foil and rolled copper foil; nickel foil; and composite foils formed by overlapping these metal foils.

[0101] (9) The electronic component according to (7) or (8), wherein the surface roughness of the metal foil is 0.001 μm or more and 0.5 μm or less.

[0102] (10) An electronic component according to any one of (7) to (9) above, wherein the particle size range of the silica particles, when measuring the particle size distribution, is such that D10 (10% cumulative) to D90 (90% cumulative) is greater than or equal to 5 nm and less than or equal to 50 nm.

[0103] (11) The electronic component according to any one of (7) to (10), wherein the silica particles are present at an interface between the metal foil and the insulating layer.

[0104] (12) An electronic component according to any one of the above (7) to (11), wherein the surface of the silica particles has a portion having a curvature greater than that calculated based on the average radius of the silica particles, and the area where the portion having a greater curvature contacts the metal foil becomes a surface having a predetermined area.

[0105] (13) The electronic component according to any one of (7) to (12), wherein the silica particles are dispersed in a plane at an interface between the insulating layer and the metal foil.

[0106] (14) The electronic component according to any one of (7) to (13), wherein the silica particles are dispersed on the main surface of the metal foil without overlapping.

[0107] (15) The electronic component according to any one of (7) to (14) above, wherein the silica particles include particles having a neck portion between the silica particles and the metal foil.

[0108] Description of Reference Numerals

[0109] 1: Metal film.

[0110] 2: Wiring board (an example of an electronic component).

[0111] 10: Metal foil.

[0112] 10a: Main surface (one example of a surface).

[0113] 11: Silica particles.

[0114] 12: Insulation layer.

[0115] 12a: Main surface.

Claims

1. A metal film, wherein: The metal film comprises a metal foil and a plurality of silicon dioxide particles having an average particle diameter of 100 nm or less. The plurality of silica particles are in contact with the surface of the metal foil.

2. The metal film according to claim 1, wherein Electrostatic attraction acts between the metal foil and the silica particles.

3. The metal film according to claim 1 or 2, wherein: The silicon dioxide particles are spherical and are in point contact with the metal foil. The portion of the metal foil that is not in contact with the silica particles is exposed.

4. The metal film according to any one of claims 1 to 3, wherein When a unit area of ​​the metal foil in a plan view is defined as 1, an area ratio of the plurality of silica particles is 1% or more and 60% or less.

5. The metal film according to any one of claims 1 to 4, wherein The metal foil contains copper or nickel as a main component.

6. The metal film according to any one of claims 1 to 5, wherein The silica particles are aggregates of a plurality of primary particles having an average particle diameter of 1 nm to 5 nm.

7. An electronic component, wherein: The electronic component comprises the metal film according to any one of claims 1 to 6 and an insulating layer. The metal foil is bonded to the insulating layer via a plurality of the silicon dioxide particles.

8. The electronic component according to claim 7, wherein The metal foil is composed of at least one metal foil selected from the group consisting of copper foils such as electrolytic copper foil and rolled copper foil; nickel foil; and composite foils in which these metal foils are stacked.

9. The electronic component according to claim 7 or 8, wherein: The surface roughness of the metal foil is 0.001 μm or more and 0.5 μm or less.

10. The electronic component according to any one of claims 7 to 9, wherein Regarding the range of the particle size of the silica particles, when the particle size distribution is measured, the range of D10 to D90 is 5 nm or more and 50 nm or less, where D10 is a 10% cumulative particle size and D90 is a 90% cumulative particle size.

11. The electronic component according to any one of claims 7 to 10, wherein The silicon dioxide particles exist at the interface between the metal foil and the insulating layer.

12. The electronic component according to any one of claims 7 to 11, wherein The surface of the silica particle has a portion having a larger curvature than that calculated from the average radius of the silica particle, and a region where the portion having the larger curvature contacts the metal foil forms a surface having a predetermined area.

13. The electronic component according to any one of claims 7 to 12, wherein The silicon dioxide particles are dispersed on a plane at an interface between the insulating layer and the metal foil.

14. The electronic component according to any one of claims 7 to 13, wherein The silica particles are dispersed on the main surface of the metal foil without overlapping each other.

15. The electronic component according to any one of claims 7 to 14, wherein Some of the silica particles have a neck portion between the silica particles and the metal foil.

Citation Information

Patent Citations

  • Substrate for printed circuit

    JP1984194487A